PENGARUH PENAMBAHAN TEPUNG MOCAF TERHADAP KUALITAS PRODUK BISKUIT - Muh Arsyad (Fakultas Pertanian Universitas Ichsan Gorontalo, 2016)
Mocaf flour is flour derived from cassava which has come throughfermentation process. The purpose of research is to determine the effect of starch Mocaf towards quality biscuits and determine the level acceptance of the panelists on the biscuits with the addition ofMocaf flour. This study has four treatment that the comparison composition between flour andMocafflour ie 100 g flour and 0 g Mocaf flour, 75 g flour and 25 g Mocaf flour, 25 g flour and 75 gMocaf flour, 0 g of flour and 100 g Mocaf flour. Parameters measured were moisture content, ash content and protein content, and organoleptic test on the texture, flavor, color and aroma of biscuits. This study used completely randomized design (RAL). These results indicate that the water content of biscuits increasealong with the increasing of Mocafflour in the biscuits production, while the protein content and ash content decreased along with the increasing of Mocaf flour. A test of the flavor, color, aroma and texture of the biscuits showed that the addition of 100 g Mocafflour more preferable.